SOLID DISPERSIONS: RESUSCITATING ORAL DELIVERY OF HYDROPHOBIC DRUGS - AGRAWAL, RUCHI; RAZA, ABID; PATEL, OM PRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This review article explores solid dispersions (SDs) as one of the suitable approaches to formulate poorly water-soluble drugs. The objective of this review on SD techniques is to explore their utility as a feasible, simple, and economically viable method for augmentation of dissolution of hydrophobic drugs. Methods: Various types of SDs are classified and compared. Use of surfactants to stabilize the SDs and their potential advantages and disadvantages has been discussed. Different techniques for preparing and evaluating SDs are appraised along with discussions on scalability and industrial production. Review of the current research on SD along with future trends is also offered. Results: Based on the various researches, SDs offer an efficient means of improving bioavailability while concurrently contributing to lower toxicity and dose-reduction. Conclusion: Solid-dispersions have been and continue to be one of the key technologies for solving the issue of poor solubility for newer hydrophobic molecules which are being discovered. This would give a new lease of life for such drugs enabling them to be delivered in an effective way.